Perilaku Pencarian Bantuan Oleh Perempuan Disabilitas Penyintas Kekerasan Seksual (Studi Kasus di Lembaga X Yogyakarta) - Widyaningtyas, Prasita Ayu; Damayanti, Rita (UI Scholars Hub, 2022)
Background. Women with disabilities are a vulnerable group who can experience sexual violence due to conditions of disability and intersecting gender inequality. Aim. Knowing the behavior of seeking help by women with disabilities who are survivors of sexual violence by using the help seeking behavior model from Liang year 2005 includes individual factors, interpersonal factors, socio-cultural factors, problem recognition, decision making to seek help, and selection of sources of support. Method. Qualitative research with a case study approach at Institution X Yogyakarta with a total of 7 informants. Result. Survivors have a false perception that sexual violence is an act of beating and not coercion. All the survivors were initially silent because of the culture that considers people with disabilities to be people who do not deserve help. Informal sources of assistance are preferred by survivors to solve problems and only some survivors continue to formal institutions. Conclusion. Survivors with good knowledge about sexual violence, have family support, and have few socio-cultural barriers will encourage survivors to seek help to formal institution